Capital inflows and income inequality: Evidence from panel VAR approach - Jinyeong Yun (Philipps-University Marburg, School of Business and Economics, 2023)
In this paper, I document empirical evidence that an external shock in capital inflows leads to an increase in income inequality in advanced economies and causes a decline in income inequality in emerging market economies. I estimate a panel VAR model with an annual dataset on 53 countries over the period 1990-2020 to study the effects of capital inflows on income inequality within countries. To distinguish the external capital inflow shocks driven by global financial conditions from other shocks, I identify the structural external shocks to capital inflows using sign restrictions. The analysis is performed separately in advanced and emerging market economies since the two groups show significant differences in the level of economic development and the degree of capital market openness. The results are statistically and economically significant. By income class, a capital inflow shock increases primarily the income share of the rich in advanced economies and the poorest half in emerging market economies. These empirical findings suggest that capital inflows have different impacts on income inequality across countries, and policymakers should pay attention to the possibility of adverse distributional effects of capital inflows.
Keywords: D63; F32; F38; 330; Capital inflows; Income inequality; Panel VAR; Sign restrictions